Reliable method of aerodynamic analysis using computational fluid dynamics and scaled models in the development process of a Very Light Airplane. Issue 1 (January 2021) - Olejnik, Aleksander; Dziubmski, Adam; Kiszkowiak, Lukasz
Abstract: In past decades a massive improvement of computational fluid dynamics (CFD) methods and the rapid increase of computational resources made it possible to simulate a lot of phenomena appearing during the flow of fluid around objects. In following paper a reliable method of aerodynamic analysis using both CFD and scaled models in the development process of a Very Light Airplane have been presented. A method of preparing a numerical model of an airplane and the aerodynamic analysis methodology have been shown. A numerical calculations using finite volume method implemented in specialized software were performed. What is more important, to perform the aerodynamic tests in wind tunnels, scaled models of an airplane have been prepared using the modern and fast manufacturing technologies, including 3D printing and CNC machining. The results have been shown in the graphs form of aerodynamic force and moment components as function of angle of attack. During research an influence of structural parts of an airplane on aerodynamic characteristics have been analyzed. The qualitative results of a flow around the aircraft body have been presented in form of parameter distribution maps on the airframe surface have been shown. Visualization of pressure distribution have been extended with path lines visualization of the flow. The research described in the paper is an example of professional and innovative approach to the subject matter.